Design study of outer rotor field excitation flux switching motor for electric vehicles - Abdull Patas, Nor Hasnati (2014)
Flux switching machines (FSMs) that consist of all flux sources in the stator have been developed in recent years. They can be categorized into three groups that are Permanent magnet (PM) FSM, field excitation (FE) FSM and hybrid excitation (HE) FSM. Among these FSMs, the FEFSM offers advantages of low cost, simple construction and variables flux control capabilities suitable for various performances. In this project is design study of outer-rotor field-excitation flux switching motor (FEFSM) with a topology of 12-slot and 10-pole configuration (12S-10P) with all active parts are located on the stator for electric vehicle application as a low-cost of non-Permanent Magnet (PM) machine. The performance of the proposed motor on the initial design and improved design are analysed based on 2-D Finite element analysis (FEA). The performance of the improvement design shows that the maximum torque is obtained 118.2165 Nm which is greater than the initial design that obtained 72.788Nm, whereas the maximum power has achieved about 77.65kW.